Mapping potential environmental impacts of alien species in the face of climate change - Sabrina Kumschick; Lysandre Journiac; Océane Boulesnane-Genguant; Christophe Botella; Robin Pouteau; Mathieu Rouget (Biological Invasions, 2025)
Risk maps are a useful tool to prioritise sites for management and allocate resources where they are most needed as they can show us where impacts of biological invasions are most likely to happen or expected to be largest. Given the pace of global changes, we need to understand not only the risks under current conditions, but future risks taking these changes into account. In this study, we use Australian acacias alien to South Africa as a case study to model their potential distribution under future climate change to map their potential impacts at the middle and end of the century and the uncertainty related to three socio-economic pathways and five climatic models. The resulting risk maps across South Africa are a pioneering attempt to combine impacts of alien species with potential future distributions. We found that although climatic suitability and therefore the risk is predicted to decrease under climate change in 51,4% of the country’s area, the opposite is predicted for 26% of the area and the highly vulnerable fynbos biome remains an area with high projected impacts. Such risk maps can help us prioritise management actions and aid the development of suitable plans to protect biodiversity under current and future climate conditions. However, they have to be interpreted with caution and we highlight some shortcomings around species distribution models in general, vulnerability of ecosystems to the potential impacts, data gaps on impacts, as well as currently benign or unknown invaders, which are not included in the projections.

Don't bite the hand that feeds you: Meta food webs help in the face of the Eltonian shortfall - Christophe Botella; Pierre Gaüzère; Louise O'Connor; Julien Renaud; Yue Dou; Catherine H. Graham; Peter H. Verburg; Luigi Maiorano; Wilfried Thuiller (Global Change Biology, 2024)

Land‐use intensity influences European tetrapod food webs - Christophe Botella; Pierre Gaüzère; Louise O'Connor; Marc Ohlmann; Julien Renaud; Yue Dou; Catherine H. Graham; Peter H. Verburg; Luigi Maiorano; Wilfried Thuiller (Global Change Biology, 2024)
Land use intensification favours particular trophic groups which can induce architectural changes in food webs. These changes can impact ecosystem functions, services, stability and resilience. However, the imprint of land management intensity on food‐web architecture has rarely been characterized across large spatial extent and various land uses. We investigated the influence of land management intensity on six facets of food‐web architecture, namely apex and basal species proportions, connectance, omnivory, trophic chain lengths and compartmentalization, for 67,051 European terrestrial vertebrate communities. We also assessed the dependency of this influence of intensification on land use and climate. In addition to more commonly considered climatic factors, the architecture of food webs was notably influenced by land use and management intensity. Intensification tended to strongly lower the proportion of apex predators consistently across contexts. In general, intensification also tended to lower proportions of basal species, favoured mesopredators, decreased food webs compartmentalization whereas it increased their connectance. However, the response of food webs to intensification was different for some contexts. Intensification sharply decreased connectance in Mediterranean and Alpine settlements, and it increased basal tetrapod proportions and compartmentalization in Mediterranean forest and Atlantic croplands. Besides, intensive urbanization especially favoured longer trophic chains and lower omnivory. By favouring mesopredators in most contexts, intensification could undermine basal tetrapods, the cascading effects of which need to be assessed. Our results support the importance of protecting top predators where possible and raise questions about the long‐term stability of food webs in the face of human‐induced pressures.

Melaleuca (Myrtaceae): Biogeography of an important genus of trees and shrubs in a changing world - Michèle B. ter Huurne; Luke J. Potgieter; Christophe Botella; David M. Richardson (South African Journal of Botany, 2023)